1999
DOI: 10.1164/ajrccm.159.3.9806130
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Clinical Assessment in the Diagnosis of Pulmonary Embolism

Abstract: To provide clinical diagnostic criteria for pulmonary embolism (PE), we evaluated 750 consecutive patients with suspected PE who were enrolled in the Prospective Investigative Study of Acute Pulmonary Embolism Diagnosis (PISA-PED). Prior to perfusion lung scanning, patients were examined independently by six pulmonologists according to a standardized diagnostic protocol. Study design required pulmonary angiography in all patients with abnormal scans. Patients are reported as two distinct groups: a first group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
218
5
39

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(264 citation statements)
references
References 28 publications
2
218
5
39
Order By: Relevance
“…Previous 13-16) structured clinical models for early pretests of the proba- [13][14][15][16] placed relatively large proportions of patients in the intermediate probability category, which was of limited utility to both physicians and patients. Furthermore, previous models used suspected PE instead of specific symptoms as the initial inclusion criterion for patient recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous 13-16) structured clinical models for early pretests of the proba- [13][14][15][16] placed relatively large proportions of patients in the intermediate probability category, which was of limited utility to both physicians and patients. Furthermore, previous models used suspected PE instead of specific symptoms as the initial inclusion criterion for patient recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] This criterion, however, lacked a clear definition because, in part, different physicians had different perceptions of suspected PE. These models, therefore, led to heterogeneous populations predicted to have PE, which undoubtedly led to variable pretest probabilities [13][14][15][16] and the low accuracy of these models. [14][15][16] Consequently, these models were of limited value in clinical practice.…”
mentioning
confidence: 99%
“…The classic findings of hemoptysis, dyspnea, and chest pain are insensitive and nonspecific for a diagnosis of PE, with fewer than 20% having this classic triad. The incidence of common symptoms in patients suspected of having PE is depicted in Table 1 [38]. One prospective observational study found that the single historical finding most sensitive for PE was unexplained dyspnea.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Table 1 shows the prevalence of various signs in patients suspected of having PE [38]. Although other studies reveal tachypnea to be the most sensitive clinical sign, it is absent in 5% to 13% of cases of PE [34,40].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Nos pacientes estáveis clinicamente, a dispnéia e a dor torácica são os sintomas mais freqüentes 42,43 . No estudo PIOPED (Prospective Investigators of Pulmonary Embolism Diagnosis) a dispnéia esteve presente em 73% e a dor torácica tipo pleurítica, em 66% dos pacientes 44 .…”
Section: Sinais E Sintomasunclassified